Meningkatkan Kreativitas Siswa dengan Menggunakan Metode Pemberian Tugas pada Mata Pelajaran Sosiologi - Nursam Lubis (Universitas Negeri Medan, 2015)
The subject of this research is 43 students at class Social Science-1 grad XI, whereas the object of the research is teaching method of tasking, and data was collected by using list of observation and questionaire. Based on pre test to 26 students, resulting 10 students (38.5 percent) obtained lower learning outcome and only 4 students (15.4 percent) reached good score with average 64.3 percent. Then in first cycle, resulting 6 students (23.1 percent) gained good predicated with average score 65.2 percent. In the second cycle, the outcome climbed to 21 students (80.8 percent) gained good predicate of creativity with 86.5 score. By questionaire in the last meeting, resulting 3 students (11.5 percent) obtained lower score and only 21 students (80.7 percent) gained good score with average score of 80.5 percent. Based on the research starting the first to second cycle, empirically have proved thart learning outcome increases significantly. Therefore using method of tasking can be elevate students creativity on the subject of Sociology at class Social Science-1 grade XI in SMA 12 of Medan.